Pemanfaatan Limbah Substrat dan Limbah Cair Kopi sebagai Media Pembibitan Tembakau Besuki - Susan Barbara Patricia SM (Universitas Sebelas Maret, 2022)
A good planting media for tobacco has the characteristics of being able to maintain moisture in plant roots, provide sufficient oxygen, and contain nutrients. Physically, a good growing media is not too dense, so it can help the formation and development of plant roots, has good aerase, not a source of disease, abundant and the price is relatively cheap. This research mixed mushroom planting media waste with animal manure and coffee liquid waste to be used as a media for tobacco seedling. The ability of the new plant media that has been created then be tested with tobacco seedling. The objectives of this study were to determine the effect of addition chicken and cow manure on the manufacture of new planting media on tobacco growth, and the effect of adding coffee liquid waste to the manufacture of new planting media on tobacco growth. Result of analysis of variance showed significant effect on parameter seedling height, diameter, and root length. The highest addition of coffee liquid waste showed the greatest seedling height. The biggest seedling stem diameter were seedling planted in media added by cow mannure. Moreover, interaction between plant media variation and coffee liquid waste also showed significantly affected the root length of tobacco seedling. Addition 40% concentration and less of coffee liquid waste to plant media made root length greater.